An update of pharmacology, efficacy, and safety of vonoprazan in acid-related disorders. (4th May 2022) - Savarino, Vincenzo; Antonioli, Luca; Fornai, Matteo; Marabotto, Elisa; Demarzo, Maria Giulia; Zingone, Fabiana; Ghisa, Matteo; Barberio, Brigida; Zentilin, Patrizia; Ribolsi, Mentore; Savarino, Edoardo
ABSTRACT: Introduction: Patients with acid-related disorders (ARDs) of the upper digestive tract remain highly prevalent and need to be continuously investigated to improve their management. Areas covered: This review provides a summary of the most recent advancements in the treatment of ARDs with particular focus on the new drugs available to overcome the unmet needs of traditional therapies. Expert opinion: Proton pump inhibitors remain the best therapy in treating ARDs, but a consistent proportion of these patients continues to present mucosal lesions or to experience symptoms despite treatment. These cases pertain mainly to the most severe forms of erosive esophagitis or to non-erosive reflux disease. Also, the increasing rate of patients with H. pylori infection not responding to eradication therapy represents a difficult clinical condition. The recent advent of a new class of antisecretory drugs, such as the potassium competitive acid blockers and, among them the most studied vonoprazan, which are characterized by a better pharmacological profile than PPIs (rapid onset of action, longer lasting acid suppression, control of nocturnal acidity), has the potential to overcome the above-mentioned unmet needs. More research should be done to assess their efficacy in Western populations and their safety in patients treated in the long term.